Comparative Analysis of the Kinematics Solution Based on the DH Method and Screw Theory. (30th January 2021) - Li, Yong-Bin; Li, Tie-Jun; Zhu, Hui-Fang; Yang, Dong; Chen, Ya-Jun; Zhang, Wen-Ming; Liu, Jian-Ming; Zhang, Tian
Abstract : The premise of analyzing and researching robot technology is to establish a proper mathematical model and then to solve it with kinematics. In this study, a self-developed humanoid hydraulically driven dual-arm robot is taken as the research object, and the DH (Denavit–Hartenberg) parameter method and the rotational exponential formula (POE) are used to solve the kinematics of the robot. The calculation results are verified by simulation. The advantages and disadvantages of the two methods are analyzed. The differences between the two methods are compared. It lays a foundation for other scholars to choose mathematical models when analyzing the mechanism in the future.